Genetic Studies of mrp, a Locus Essential for Cellular Aggregation and Sporulation of Myxococcus xanthus - Sun, Hong (American Society for Microbiology, 2001)
Under starvation conditions, Myxococcus xanthus undergoes a complex developmental process which includes cellular aggregation and sporulation. A transposon insertion mutant (the Tn5-Ω280 mutant) with defects in both aggregation and sporulation was analyzed in this study. The Tn5-Ω280 mutant was found to have a disrupted NtrC-like response regulator designated Myxococcus regulatory protein B (mrpB). Further sequencing analyses revealed a histidine kinase homolog (mrpA) immediately upstream of mrpB and a cyclic AMP receptor protein-like transcriptional regulator (mrpC) downstream of mrpB. In-frame deletion analyses revealed that both the mrpB and mrpC genes were required for cellular aggregation and sporulation but that only mrpA was required for sporulation only. Site-specific mutagenesis of the putative phosphorylation site of MrpB, D58, showed that a D58A mutation caused defects in both aggregation and sporulation but that a D58E mutation resulted in only a sporulation defect. Further genetic and molecular analyses with reporter genes and reverse transcription-PCR indicated that mrpA and mrpB are cotranscribed but that mrpC is transcribed independently and that all of these genes are developmentally regulated. In addition, MrpB is essential for transcription of mrpC and MrpC regulates its own transcription. These data indicate that Mrp proteins are important components required for M. xanthus development. The complicated interaction between Mrp proteins may play an important role in regulating developmental gene expression in M. xanthus.